Endoskopische Resektion beim Frühkarzinom des gastroösophagealen Überganges - Kähler, Georg (Der Chirurg, 2012)
The endoscopic examination of the gastroesophageal junction focuses on confirmation of neoplastic lesions or precursors. Recent technical advances, such as high resolution video endoscopes and chromoendoscopy may improve the sensitivity of endoscopic diagnosis. Biopsies are still a necessary part of the examination, however, they may be not representative for the lesion and should be replaced by a complete endoscopic resection wherever possible.If the histopathological examination reveals a well differentiated carcinoma without microlymphatic and microvenous infiltration with tumor-free resection margins which is limited to the mucosa, endoscopic resection can be regarded as curative.While tumor infiltration depth and differentiation are determined by the tumor biology, complete resection can be achieved by a sophisticated endoscopic technique which requires vast experience and extensive equipment.